Wealth Effect Of International Investment Announcements: Evidence From Developing Market - Amin Noordin, Bany Ariffin; Mat Nor, Fauzias (Asian Academy of Management (AAM), 2006)
This research provides evidence on the efficiency of one of the fastest developing and largest emerging securities market (Kuala Lumpur Stock Exchange, KLSE) in the Asia Pacific rim with respect to foreign investment announcements. Specifically, our study focuses on international investment announcements made in 1990 through 2000 for firms listed on the main board of the KLSE of Malaysia. The result shows that the announcements of foreign investment produce a significant positive daily abnormal return surrounding the event period. This implies that foreign investment announcements made by listed Malaysian firms do contain new relevant information which may creates market movements. At the same time, since the reaction is significantly positive, this implies that investors generally favor the international investment efforts of Malaysian firms listed at KLSE. In addition, it is also discovered that the economic development of the target country does influence the wealth creation process.